The tale of two research communities: The diffusion of research on productive efficiency - Finn R. Førsund; Nikias Sarafoglou (University of Oslo, Department of Economics, 2003)
The field of theoretical and applied efficiency analysis is pursued both by economists and people from operational research and management science. Each group tends to cite a different paper as the seminal one. Recent availability of electronically accessible databases of journal articles makes studies of the diffusion of papers through citations possible The conventional wisdom that the seminal paper within economics lay dormant for two decades, and that efficiency studies only got rolling after the operational research paper appeared, is shown to be wrong. Citation peaks have been found to be typically five to seven years, with a long tailing off. Both seminal papers followed quite different diffusion patterns. Research strands inspired by the seminal paper within economics are identified and followed by citation analysis. In recent years a weak trend toward convergence of the two camps into a common network for efficiency and productivity analyses is documented.
Keywords: B21; D24; 330; Bibliometric methods; Farrell efficiency measures; DEA; Wissenschaftliches Arbeiten; Informationseffizienz; Publikationsanalyse; Data-Envelopment-Analyse